Pedagogical technology of regression and correlation analyses in pedagogical research. - VOLOVIK, Pavel (Continuing Professional Education: Theory and Practice, 2019)
The paper deals with the analysis of pedagogical phenomena correlation and statistic estimation of pedagogical indexes, which allow to make correlation connections between variables characterizing pedagogical phenomena and processes. The connections classifi cation due to the form (linear, non-linear), the differences between them and technique for construction of relations of linear and non-linear correlation connections are presented